A characterization of the identity function with some property on GP - Nammanee, Kamonrat (วารสารวิชาการวิทยาศาสตร์และวิทยาศาสตร์ประยุกต์, 2022)
We prove that if a multiplecative function f satisfies. Then f is the identity function.